PENGARUH PENGGUNAAN MEDIA TIME LINE CHART TERHADAP HASIL BELAJAR IPS TEMA PAHLAWANKU KELAS IV SEKOLAH DASAR - Fajar Nur Yasin (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
This study aimed to determine the effect of the use of media time line chart of the results of social studies. The hypothesis of this study was the effect of the use of media time line chart of the results of social studies the theme Pahlawanku of fourth grade elementary school. The method used quasi-experimental design nonequivalent (pretest and posttest) control group. The sample in this study is the fourth grade students as many as 41 people. The instrument used was the result of social studies in the form of matter pretest and posttest. Analysis of data using the t test. Results hypothesis by using t-test showed that there is a significant impact on students' learning outcomes IPS, with a significance level of 5% of 0.05 with sig. (2-tailed) was 0,000. If seen t table of 1.684 (N = 41) with a t value of 7.141.